How many older adults receive drugs of questionable clinical benefit near the end of life? A cohort study. (September 2019) - Morin, Lucas; Wastesson, Jonas W; Laroche, Marie-Laure; Fastbom, Johan; Johnell, Kristina
Background: The high burden of disease-oriented drugs among older adults with limited life expectancy raises important questions about the potential futility of care. Aim: To describe the use of drugs of questionable clinical benefit during the last 3 months of life of older adults who died from life-limiting conditions. Design: Longitudinal, retrospective cohort study of decedents. Death certificate data were linked to administrative and healthcare registries with national coverage in Sweden. Setting: Older adults (≥75 years) who died from conditions potentially amenable to palliative care between 1 January and 31 December 2015 in Sweden. We identified drugs of questionable clinical benefit from a set of consensus-based criteria. Results: A total of 58, 415 decedents were included (mean age, 87.0 years). During their last 3 months of life, they received on average 8.9 different drugs. Overall, 32.0% of older adults continued and 14.0% initiated at least one drug of questionable clinical benefit (e.g. statins, calcium supplements, vitamin D, bisphosphonates, antidementia drugs). These proportions were highest among younger individuals (i.e. aged 75–84 years), among people who died from organ failure and among those with a large number of coexisting chronic conditions. Excluding people who died from acute and potentially unpredictable fatal events had little influence on the results. Conclusion: A substantial share of older persons with life-limiting diseases receive drugs of questionable clinical benefit during their last months of life. Adequate training, guidance and resources are needed to rationalize and deprescribe drug treatments for older adults near the end of life.